ANALYSIS OF ANTIBODY RESPONSE TO SARS-COV-2 VACCINATION AND ITS RELATION WITH AGE IN PATIENTS AT PRODIA ARTERY - Mubayinah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
One of the efforts to overcome Covid-19 is the vaccination program. Anti-SARS CoV-2 is an antibody against Sars-CoV-2 formed due to previous exposure to Covid-19 infection or due to the administration of the Covid-19 vaccine. This study aims to determine the average number of Anti-Sars-CoV-2 respondents vaccinated against Covid 19 and the relationship between age and the number of Anti-Sars-CoV-2. This research is a quantitative study with an observation method with a cross-sectional approach which means looking for a relationship between the independent variable and the dependent variable, and this study uses secondary data. The results of this study indicate that more than half of the respondents (52%) are male, while based on the most common age group is 36-45 (48%), the average value of Anti Sars Cov-2 is 92.76%, with the lowest value 5.1 U/ml and the highest value 250 U/ml, statistical test results show that there is no age relationship with levels of Anti-ars-Cov-2. Suggestion: Further research is needed by looking at other predictors that affect levels of Anti Sars-Cov-2.